KEWENANGAN PENYELESAIAN SENGKETA KEPAILITAN YANG DALAM PERJANJIANNYA TERCANTUM KLAUSUL ARBITRASE - Asri Alvionita, Ni Made; Bagiastra, I Nyoman (Kertha Semaya : Journal Ilmu Hukum, 2014)
In a trade practice of the community, an agreement between the debtor and the creditor, often containing an arbitration clause. When disputes arise bankruptcy, appears polemic which agency has the authority to resolve the dispute bankruptcy, whether the Commercial Court or Arbitration. The purpose of this study was to determine which agency has the authority to resolve disputes in the event of any bankruptcy arbitration clause in the agreement. The method used in the writing of a scientific journal is a normative study. Under the Bankruptcy Act, the Commercial Court is an institution of the most competent to resolve disputes in bankruptcy despite specifying the arbitration clause in the agreement, because arbitration is considered as extra judicial authority which can not be ruled out as an extra ordinary commercial court.
Keywords: Dispute Resolution, Bankruptcy, Court, Arbitration